2011
DOI: 10.1016/j.jinorgbio.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and biological activity of trans-platinum(II) complexes with chloroquine

Abstract: Three platinum-chloroquine complexes, trans-Pt(CQDP)2(I)2 [1], trans-Pt(CQDP)2(Cl)2 [2] and trans-Pt(CQ)2(Cl)2 [3], were prepared and their most probable structure was established through a combination of spectroscopic analysis and density functional theory (DFT) calculations. Their interaction with DNA was studied and their activity against 6 tumor cell lines was evaluated. Compounds 1 and 2 interact with DNA primarily through electrostatic contacts and hydrogen bonding, with a minor contribution of a covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
5
23
0
Order By: Relevance
“…Only the complexes 2, 5 and 7 show cytostatic effects at doses appreciably lower in comparison with cisplatin, chloroquine and doxorubicin under the same conditions. Interestingly, the complex 7 was the most active, with an of CQ enhances the biological activity of the metal complexes, as reported previously[6,8]. Under an inverted microscope, cell shape and changes in it can be observed clearly.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Only the complexes 2, 5 and 7 show cytostatic effects at doses appreciably lower in comparison with cisplatin, chloroquine and doxorubicin under the same conditions. Interestingly, the complex 7 was the most active, with an of CQ enhances the biological activity of the metal complexes, as reported previously[6,8]. Under an inverted microscope, cell shape and changes in it can be observed clearly.…”
supporting
confidence: 84%
“…In the spectroscopic titrations, in the presence of ctDNA, all complexes showed decreases in absorption (hypochromism-%H) thus determining the constant of interaction (Kb 2 , Kb 1 ) by a nonlinear Scatchard curve ( Figure 14S). The Kb 1 and Kb 2 ( Table 5) are within the accepted range for compounds considered to interact with DNA [6]. Overall, complexes 1-5 present low hypochromism and also low Kb 1 and Kb 2 values compared with their analogous with CQ, and the overall positive charge could offer an interacts electrostatics with the phosphate groups.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
“…A multiplet of H of C5 was found at δ 7.49-7.51. In 13C NMR, the benzyl carbon C1 at δ 47.84, C2 at 138.34, C3 and C7 found at 127.57-127.14, C4 and C6 found between 128.73-128.36 and C5 found at 128.1 (ESI † Figures S1 and S2) [21,22]. The +ve ESI mass spectra of Pd complex have found [M+1] for complex confirming its molecular mass.…”
Section: Anticancer Activitymentioning
confidence: 83%
“…The IR spectrum of the complex shows peaks clearly associated with the presence of coordinated CQDP. In the 1 H-NMR spectrum, the 1 H chemical shift variation of each signal with respect to that of the free ligand reported previously 19) was similar and used to deduce the mode of bonding of CQDP to the metal. The largest shift with respect to the free ligand (CQDP) was observed for NH and H1′ as they are the nearest protons to the N-atom bonded to the metal, indicating that CQDP is bound to platinum through the nitrogen of the secondary amine.…”
Section: Resultsmentioning
confidence: 99%
“…PtCQ is a trans platinumchloroquine complex that shows therapeutic effects against the chloroquine-resistant malaria parasite, 19) but many fundamental properties of PtCQ, such as drug solubility, remain poorly investigated, although it was reported that PtCQ dissolves in dimethyl sulfoxide (DMSO). We therefore investigated methods for efficiently loading PtCQ into liposomes and first characterized the handling properties of PtCQ.…”
mentioning
confidence: 99%